Innovation in education through lesson study: incorporating disaster risk reduction in mathematics lesson to inculcate tsunami awareness - Khalid, Madihah (2014)

(untitled)
Measures for disaster risk reduction (DRR) can be integrated into a nation’s education system in order to help build long term resilience of the people and education system. Consequently, children can be taught about natural disasters so that they are aware of calamities and be reminded of Allah’s greatness. Being exposed to emergency preparedness education may even enable them to save their live and other people’s lives . This paper reports on a research that aims to inculcate students’ awareness of natural disasters through a mathematics lesson that focus on saving one’s life from tsunami, via lesson study. The lesson was repeated with two other classes and students were given pre and post test to determine their different level of understanding before and after the lesson. The year 5 students were found to have benefited from their lesson in terms of their increased knowledge of tsunami, and their ability to apply their knowledge on rates in finding the best alternative to the problem posed on saving their life. Students in the second repeat lesson was found to have significantly higher understanding of tsunami and rate, compared to the first and third classes due to some identified reasons. Finally, lesson study was able to help enhance teachers’ pedagogical content knowledge and help them to produce lesson plans that incorporate student-centred, authentic lesson that also integrate awareness of natural calamities, use of technology and students’ creativity in problem solving